2020
DOI: 10.1016/j.jaap.2019.104756
|View full text |Cite
|
Sign up to set email alerts
|

Fast pyrolysis with fractional condensation of lignin-rich digested stillage from second-generation bioethanol production

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…5% total mass flow) of the nitrogen flow was fed from the top of the reactor to purge the top of the reactor and thus prevent vapors from accumulating and condensing on the top reactor walls. The LRDS was placed in a nitrogen-purged vibration-assisted lock hopper (3) and then fed into the feeding screw (2). Approximately 10 g of the LRDS was fed intermittently every 10 min to achieve a biomass feeding rate of ca.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5% total mass flow) of the nitrogen flow was fed from the top of the reactor to purge the top of the reactor and thus prevent vapors from accumulating and condensing on the top reactor walls. The LRDS was placed in a nitrogen-purged vibration-assisted lock hopper (3) and then fed into the feeding screw (2). Approximately 10 g of the LRDS was fed intermittently every 10 min to achieve a biomass feeding rate of ca.…”
Section: Methodsmentioning
confidence: 99%
“…6 Previous work indicated that LRDS could be pyrolyzed successfully (because of the presence of residual carbohydrates) with staged condensation to produce separate heavy and aqueous pyrolysis liquids, in addition to biochar and noncondensable gases (NCGs). 2 One of the anticipated drawbacks in fast pyrolysis of LRDS is the chemical instability of the produced pyrolysis liquids because of the presence of reactive aldehydes and phenolics that can undergo repolymerization. 7−9 The heavy phase of pyrolysis liquid also contains a large amount of high-molecularweight compounds, in the form of dimers, trimers, and oligomeric phenols, 7,10 making the heavy pyrolysis liquid a waxy, highly viscous phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The operating conditions are as follows temperature (medium-high (700 -1000 °C), shortest residence time and fastest heating rate. Yields of outputs are: (1) liquid condensate (10 -20%), ( 2) gases (60 -80%) and ( 3) char (10 -15%) (Priharto et al 2020).…”
Section: Pyrolysismentioning
confidence: 99%
“…It is predominantly composed of the polysaccharide cellulose, a class of polysaccharides called hemicelluloses, and the aromatic polymer, lignin ( Marriot et al, 2016 ). These polymers can then be converted via chemical or biological routes into fuels and other valuable chemicals that are conventionally derived from fossil resources ( van Putten et al, 2013 ; Li and Takkellapati, 2018 ; Baral et al, 2019 ; Genuino et al, 2019 ; Priharto et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%